Chemoenzymatic Dynamic Kinetic Resolution of Primary Benzylic Amines using Pd0‐CalB CLEA as a Biohybrid Catalyst. Issue 39 (24th June 2019) - Gustafson, Karl P. J.; Görbe, Tamás; de Gonzalo‐Calvo, Gonzalo; Yuan, Ning; Schreiber, Cynthia L.; Shchukarev, Andrey; Tai, Cheuk‐Wai; Persson, Ingmar; Zou, Xiaodong; Bäckvall, Jan‐E.
Abstract: Herein, we report on the use a biohybrid catalyst consisting of palladium nanoparticles immobilized on cross‐linked enzyme aggregates of lipase B of Candida antarctica (CalB CLEA) for the dynamic kinetic resolution (DKR) of benzylic amines. A set of amines were demonstrated to undergo an efficient DKR and the recyclability of the catalysts was studied. Extensive efforts to further elucidate the structure of the catalyst are presented. Abstract : A biohybrid catalyst was used for efficient dynamic kinetic resolution (DKR) of amines to give amides in good to high yields and high enantioselectivity (up to 98 % ee ). The biohybrid catalyst consists of cross‐linked enzyme aggregates of Candida Antarctica lipase B and nanopalladium particles. The hybrid catalyst was characterized by XPS and electron microscopy.